1999
DOI: 10.1002/(sici)1520-6300(199909/10)11:5<598::aid-ajhb3>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Peripartum cocaine use and adverse pregnancy outcome

Abstract: The objective of the study was to analyze possible adverse effects of peripartum cocaine use on maternal and fetal outcomes. Informed consent was given by 720 (97%) of 740 women who delivered consecutively at a large urban public hospital to test an umbilical cord blood sample for the presence of non‐medically administered drugs of abuse and alcohol and to be interviewed for the study. Samples were tested for the presence of a cocaine metabolite (benzoylecgonine‐BZE) by radioimmunoassay. The presence of other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Controlling for individual-level characteristics, including prenatal care, alcohol, and tobacco use, they found that crack cocaine use (determined from urine tests) was positively associated with low birth weight (approximately a 9 percentage point increase). Little et al (1999) found a positive association between prenatal cocaine use (determined by blood samples) and low birth weight (approximately 10 percentage points) among all mothers giving birth in one hospital in Dallas, TX over a three-week period. The sample consisted of 101 mothers who used cocaine but no other drug and 469 who used no drugs.…”
Section: Prenatal Illicit Drug Usementioning
confidence: 99%
“…Controlling for individual-level characteristics, including prenatal care, alcohol, and tobacco use, they found that crack cocaine use (determined from urine tests) was positively associated with low birth weight (approximately a 9 percentage point increase). Little et al (1999) found a positive association between prenatal cocaine use (determined by blood samples) and low birth weight (approximately 10 percentage points) among all mothers giving birth in one hospital in Dallas, TX over a three-week period. The sample consisted of 101 mothers who used cocaine but no other drug and 469 who used no drugs.…”
Section: Prenatal Illicit Drug Usementioning
confidence: 99%
“…This factor consists of binge drinking (defined as five or more alcoholic drinks on one occasion) in the past month, current cigarette smoking, and illicit drug use in the past month. Each of these behaviors has been linked with adverse pregnancy outcomes, particularly low birthweight (Little et al 1999; Parazzini et al 2003; Centers for Disease Control and Prevention 2004; Shankaran et al 2004).…”
mentioning
confidence: 99%
“…Chronic frequent use may result in toxic paranoid psychosis. Studying cocaine use without other substances of abuse, Little et al 33 found a 2% rate of abruption (a 15 fold increase) and OR of 2.0 for birthweight less than 2500g. 30 The impact of cocaine on the fetus has been extensively studied.…”
Section: Cocainementioning
confidence: 99%